2012 IEEE International Symposium on a World of Wireless, Mobile and Multimedia Networks (WoWMoM) 2012
DOI: 10.1109/wowmom.2012.6263710
|View full text |Cite
|
Sign up to set email alerts
|

Predictive buffering for streaming video in 3G networks

Abstract: Abstract-This paper presents a multimedia streaming service in a mobile (3G) environment that, in addition to in-band congestion signals such as packet losses and delay variations, receives congestion cues from a Network Coverage Map Service (NCMS) to make rate-control decisions. The streaming client routinely queries the NCMS to assess the network conditions at future locations along its expected path. The streaming client may ask the streaming server for short-term transmission bursts to increase pre-bufferi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 23 publications
0
21
0
Order By: Relevance
“…Recently some video delivery systems associated with location information have been proposed [7,18,22,17]. Curcio et al [7] predicted network bandwidth for the future locations and adjusted the buffering parameters.…”
Section: Location-aided Video Delivery Systemmentioning
confidence: 99%
“…Recently some video delivery systems associated with location information have been proposed [7,18,22,17]. Curcio et al [7] predicted network bandwidth for the future locations and adjusted the buffering parameters.…”
Section: Location-aided Video Delivery Systemmentioning
confidence: 99%
“…When streaming video while commuting, this kind of long-term planning is possible using a location-based bandwidth lookup service for bitrate planning [10,50]. Subsequently, Singh et al [51] proposed a similar geopredictive service as a network coverage map service. To evaluate such a service, we built a time-locationbandwidth database for multiple commute routes and used this for long-term planning of adaptive HTTP streaming sessions.…”
Section: Bandwidth Predictionmentioning
confidence: 99%
“…Hung et al [14] proposed a video streaming control mechanism based on location to overcome signal variations in train tunnels and underground areas. Geo-location frameworks that have the ability to predict future network conditions based on a bandwidth lookup service and similar concepts can be found in [15], [16], [17], [18], [19]. Acharya et al [20] evaluated rateadaptation in a vehicular network based on signal strength and throughput at a location as an indicator for congestion.…”
Section: Introductionmentioning
confidence: 99%
“…Acharya et al [20] evaluated rateadaptation in a vehicular network based on signal strength and throughput at a location as an indicator for congestion. Curcio et al [15] and Singh et al [16] suggested server-side prediction algorithms for RTP streaming. Curcio et al [15] suggested a framework with a predictive server which obtains: route, speed, location and throughput from the client.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation